UNSUR BUNYI DALAM BUKU KUMPULAN PUISI TIDAK ADA NEW YORK HARI INI KARYA M. AAN MANSYUR - Yudha, Feizal Mandala; Nurizzati, Nurizzati; Hayati, Yenni (Universitas Negeri Padang, 2019)
This study aimed to describe and analyze the form and use of sound in the Poetry Collection Book Tidak Ada New York Hari Ini by M. Aan Mansyur. To achieve these objectives the theory is used: (1) the nature of poetry, (2) theory of structuralism, (3) elements of poetry building, (4) sound elements in poetry, (5) alliteration and aconance, (6) cacophony and efoni, (7) anaphora and epiphora, and (8) the function of sound in poetry. Based on the analysis in the poetry collection, There is Tidak Ada New York Hari Ini, the work of M. Aan Mansyur, found 14 sounds of alliteration, 24 sounds of aconance, 17 sounds of cacophony, 23 sounds of ephony, 10 sounds of anaphora and 2 sounds of epiphora. There are 4 functions of the use of sound elements, namely: (1) expressive energy, (2) giving suggestions to the reader, (3) means of musicality, and (4) providing an atmosphere / special impression.Keyword: form, exploiting of sound, anthology poems, Tidak Ada New York Hari Ini, M. Aan Mansyur, sound.